The influence of visual attention on letter recognition and reading acquisition in Arabic - Ghandour, Alaa; Trouche, Emmanuel; Guillo, Dominique; Valdois, Sylviane (Frontiers in Psychology, 2025)
IntroductionThe involvement of phonological awareness (PA), rapid automatized naming (RAN) and letter knowledge (LK) in Arabic reading achievement is well established, but evidence for a unique contribution of visual attention span (VAS) remains limited. Studies in Indo-European languages have reported a direct and unique influence of VAS on reading, a relationship that might also be expected in Arabic. However, the recognition of the complex Arabic letters may require substantial attentional resources, thereby reducing the direct contribution of VAS to reading.MethodsWe assessed PA, RAN, LK and VAS in Arabic-speaking beginning readers, along with their reading fluency for both nonsense syllables and real words.ResultsStrong relationships were found between all four predictors and both reading outcomes. LK and VAS were also substantially related. PA and VAS were unique predictors of reading, independent of RAN. However, the direct link between VAS and reading disappeared once LK was included as an additional predictor. VAS then only contributed indirectly to reading through its influence on LK.DiscussionThese findings suggest that a large share of attentional resources is required for the parallel, fine-grained processing of the multiple visual features of Arabic letters, thus taxing the attentional resources available for processing higher-order units. We therefore argue that the relationship between VAS and reading is modulated by the language script.